GMOS, INSTITUTIONAL RISKS, SOCIAL RISKS , REFLEXIVITY, AND CHANGE. A COMPARISON OF FRANCE AND CANADA BETWEEN 1980 AND 2001. - Chiasson, Christine (My University, 2011)
What is the political role of risk? What is its role in the power structures of today’s societies? And how can understanding its role lead to a better understanding of political change? This research is inspired by the students of late modernity who argue that the way we are dealing with risk is nowadays structuring culture, society and politics. According to these conceptions of late modernity, risk and political change are closely intertwined through the idea of reflexivity, a process of self-confrontation of a society with its own rules and institutions. This study builds on this theorization of risk and aims to discover why France and Canada, even though they were facing similar technological challenges, were progressively taken along different paths when it comes to regulating GMOs. This study has found that major differences in risk related discourse and in the strategies adopted to manage social risks are factors in explaining different policy outcomes. In addition, it shows that differences in institutional risks management also contribute to the explanation. The comparison of the French and Canadian cases has indeed revealed that, if risks can create significant pressures in favour of institutional and political change, governments may in turn possess the necessary leverage to prevent reflexivity. This comparative analysis exposed that this capacity to manage institutional risk by controlling discourse and preventing reflexivity is related to the characteristics of such core democratic institutions as the parliament, the public administration, the press, and civil society.
Keywords: GMOs; agricultural biotechnologies; institutional risks; discourse analysis; network analysis; political change; Comparative Politics; Public Policy; Comparative Politics